Findings of the Association for Computational Linguistics: NAACL 2022 2022
DOI: 10.18653/v1/2022.findings-naacl.67
|View full text |Cite
|
Sign up to set email alerts
|

Learning Rich Representation of Keyphrases from Text

Abstract: In this work, we explore how to train taskspecific language models aimed towards learning rich representation of keyphrases from text documents. We experiment with different masking strategies for pre-training transformer language models (LMs) in discriminative as well as generative settings. In the discriminative setting, we introduce a new pre-training objective -Keyphrase Boundary Infilling with Replacement (KBIR), showing large gains in performance (upto 8.16 points in F1) over SOTA, when the LM pre-traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Song et al [217] evaluated ChatGPT on multiple datasets from news and scientific literature domains having both short and long documents. Experiment results showed that ChatGPT outperforms KeyBART [227], the SOTA model, on all the datasets.…”
Section: Keyphrase Generationmentioning
confidence: 95%
See 2 more Smart Citations
“…Song et al [217] evaluated ChatGPT on multiple datasets from news and scientific literature domains having both short and long documents. Experiment results showed that ChatGPT outperforms KeyBART [227], the SOTA model, on all the datasets.…”
Section: Keyphrase Generationmentioning
confidence: 95%
“…The primary advantage of KPG over keyphrase extraction is the ability to generate both extractive and abstractive keyphrases. Keyphrase generation is approached as a sequence-to-sequence generation task [12], [226], [227] in the existing works. The current state-of-the-art model for keyphrase generation is, Key-BART [227], which is based on BART and trained using the text-to-text generation paradigm.…”
Section: Keyphrase Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The task of keyphrase generation is introduced to predict both present and absent keyphrases. (Swaminathan et al, 2020), hierarchical decoding (Chen et al, 2020b), graphs (Ye et al, 2021a), dropout (Ray Chowdhury et al, 2022), and pretraining (Kulkarni et al, 2022;Wu et al, 2022a) to improve keyphrase generation. Furthermore, there have been several attempts to unify KE and KG tasks into a single learning framework.…”
Section: Keyphrase Generationmentioning
confidence: 99%
“…Previous KPE works include supervised and unsupervised approaches. Supervised approaches model KPE as sequence tagging (Sahrawat et al, 2019;Alzaidy et al, 2019;Martinc et al, 2020;Santosh et al, 2020;Nikzad-Khasmakhi et al, 2021) or sequence generation tasks Kulkarni et al, 2021) and require large-scale annotated data to perform well. Since KPE annotations are expensive and largescale KPE annotated data is scarce, unsupervised KPE approaches, such as TextRank (Mihalcea and Tarau, 2004), YAKE (Campos et al, 2018), Em-bedRank (Bennani-Smires et al, 2018), are the mainstay in industry deployment.…”
Section: Introductionmentioning
confidence: 99%